Chain end-group selectivity using an organometallic Al(iii)/K(i) ring-opening copolymerization catalyst delivers high molar mass, monodisperse polyesters. Issue 29 (13th July 2022) - Diment, Wilfred T.; Williams, Charlotte K.
Abstract : A heterodinuclear Al(iii )/K(i ) organometallic ring-opening copolymerization catalyst shows exceptional rates, end-group selectivity and good loading tolerance to deliver monodisperse polyesters with molar masses up to 91 kg mol −1 . Abstract : Polyesters are important plastics, elastomers and fibres; efficient and selective polymerizations making predictable, high molar mass polymers are required. Here, a new type of catalyst for the ring-opening polymerization (ROCOP) of epoxides and anhydrides combines unusually high chain end-group selectivity, fast rates, and good molar mass control. The organometallic heterodinuclear Al(iii )/K(i ) complex, applied with a diol, is tolerant to a range of epoxides/phthalic anhydride and produces only α, ω-hydroxyl telechelic polyesters with molar masses from 6–91 kg mol −1, in all cases with monomodal distributions. As proof of its potential, high molar mass poly(vinyl cyclohexene oxide- alt -phthalic anhydride) (91 kg mol −1 ) shows 5× greater flexural strain at break ( ε b = 3.7%) and 9× higher maximum flexural stress ( σ f = 72.3 MPa) than the previously accessed medium molar mass samples (24 kg mol −1 ). It is also enchains phthalic anhydride, vinyl cyclohexene oxide and ε-decalactone, via switchable catalysis, to make high molar mass triblock polyesters (81 kg mol −1, Đ = 1.04). This selective catalyst should be used in the future to qualify the properties of these ROCOP polyesters and to tune (multi)block polymer structures.